A branched-chain organic ammonium salt-containing electrolyte for low-impedance aluminum electrolytic capacitors

CN123017743APending Publication Date: 2026-10-30SHENZHEN ZEASSET ELECTRONIC TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611348701.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-09-02
Publication Date
2026-10-30

AI Technical Summary

Technical Problem

[0004]但是,上述技术方案大多属于导电盐、溶剂和添加剂之间的常规拼配,即导电盐主要负责提高电导率,溶剂主要负责调节黏度和溶解性,硼系、磷系或吸氢组分主要分别承担耐压、抑水合和吸氢作用

Benefits of technology

[0018]本发明的有益效果是:本发明提供的低阻抗铝电解电容器用含支链有机铵盐电解液,通过含醚氧二羧酸、支链长链二羧酸和支链有机胺形成含支链有机铵盐导电体系,使该导电体系中同时含有支链有机铵阳离子、含醚氧二羧酸根、支链长链二羧酸根以及未中和羧基。支链有机铵阳离子在电解液体相中能够与二羧酸根形成可解离离子对,含醚氧二羧酸根有利于提高离子解离和链段柔性,支链长链二羧酸根有利于提高耐热稳定性,而支链有机铵阳离子的支链烃基屏蔽端能够阻隔二羧酸盐的有序结晶堆积,从而在隔离纸孔隙及电解液体相中形成更加连续、稳定的离子导电通道,降低铝电解电容器的等效串联电阻。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN123017743A_ABST
    Figure CN123017743A_ABST
Patent Text Reader

Abstract

The application discloses a branched-chain organic ammonium salt electrolyte for low-impedance aluminum electrolytic capacitors, which comprises, by weight, a composite solvent, an ether-oxygen-containing dicarboxylic acid, a branched-chain long-chain dicarboxylic acid, a branched-chain organic amine, a boron-containing polyhydroxy complex component, a phosphorus-containing hydration-inhibiting component, a hydrogen-absorbing stabilizing component and a free radical inhibiting component. The branched-chain organic ammonium salt conductive system is formed by the ether-oxygen-containing dicarboxylic acid, the branched-chain long-chain dicarboxylic acid and the branched-chain organic amine, and the system contains branched-chain organic ammonium cations, dicarboxylic acid radicals and unneutralized carboxyl groups, and the neutralization degree of the carboxyl groups is 52% to 78%. The unneutralized carboxyl groups and the boron-containing polyhydroxy complex component form complex sites at anodic oxide film defects, the branched-chain organic ammonium cations form hydrogen bond association with the unneutralized carboxyl groups in the complex sites through hydroxyl groups or ether-oxygen association ends, and form synergic association with the boron-containing polyhydroxy complex component, so that the branched-chain organic ammonium cations are directionally enriched to form an interface orientation layer, the liquid retention, hydration inhibition, hydrogen-absorbing stabilization and repair effects at the defects are realized, and the low-impedance stability and high-temperature life of the capacitor are improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to an electrolyte, specifically to a branched organic ammonium salt electrolyte for low-impedance aluminum electrolytic capacitors. Background Technology

[0002] Aluminum electrolytic capacitors are widely used in switching power supplies, frequency converters, automotive electronics, communication power supplies, and industrial control due to their large capacitance, low cost, and wide applicable voltage range. As electronic devices evolve towards higher frequencies, smaller sizes, and higher power densities, aluminum electrolytic capacitors often need to withstand larger ripple currents and higher operating temperatures in practical applications. This necessitates that the electrolyte possess low equivalent series resistance, high conductivity stability, good heat resistance, and a long service life.

[0003] As a crucial working medium for aluminum electrolytic capacitors, the electrolyte's conductivity, liquid retention capacity, oxide film stabilization, and side reaction suppression capabilities directly affect the capacitor's impedance, loss tangent, leakage current, withstand voltage, and lifespan. Existing low-impedance aluminum electrolytic capacitor electrolytes typically employ high-conductivity ammonium carboxylate salts, quaternary ammonium salts, imidazolium salts, or other organic salts as conductive salts, combined with composite solvents such as ethylene glycol, γ-butyrolactone, sulfolane, and amide solvents to reduce electrolyte viscosity and increase ion dissociation, thereby lowering impedance. Simultaneously, to improve high-temperature lifespan, existing technologies also add additives such as borates, phosphate esters, nitro compounds, and quinoline compounds to improve flashover voltage, inhibit hydration reactions, or reduce hydrogen evolution.

[0004] However, most of the aforementioned technical solutions involve conventional combinations of conductive salts, solvents, and additives. The conductive salts primarily improve conductivity, the solvents regulate viscosity and solubility, and boron-based, phosphorus-based, or hydrogen-absorbing components mainly handle voltage resistance, hydration suppression, and hydrogen absorption, respectively. While these components can achieve some performance synergy, their action paths are relatively independent, making it difficult to achieve adaptive synergistic regulation across different operating states of aluminum electrolytic capacitors. Especially under high-frequency ripple current or leakage current, localized defects in the anodic oxide film are prone to problems such as temperature rise, acid value changes, aluminum ion migration, and localized electrolyte drying. Although existing low-resistance electrolytes can provide high ion conductivity in the bulk phase, they often fail to actively accumulate and form a stable interfacial liquid-retaining layer at oxide film defects. This results in the defect area continuously bearing electric field and thermal stress, leading to increased leakage current, impedance rebound, increased gas production, and reduced lifespan.

[0005] Furthermore, existing technologies typically increase the content of conductive salts or use salt systems with higher dissociation degrees to improve the low impedance performance of electrolytes. However, excessively high conductive salt content can easily lead to low-temperature crystallization, increased viscosity, or exacerbated side reactions at high temperatures. On the other hand, adding more borates or phosphates to improve heat and pressure resistance may increase system viscosity and hinder ion migration, thus affecting the low impedance performance. Therefore, existing technologies struggle to achieve a balance between low impedance, heat stability, interfacial electrolyte retention, and oxide film repair.

[0006] Therefore, there is an urgent need to provide a branched organic ammonium salt electrolyte for low-impedance aluminum electrolytic capacitors. This electrolyte not only forms continuous ionic conductive channels in the electrolyte liquid phase, reducing the equivalent series resistance of the capacitor, but also achieves directional enrichment in the defect region of the anodic oxide film. Furthermore, it interacts with complexing components, hydration-suppressing components, and hydrogen-absorbing stabilizing components to create a synergistic effect of liquid retention, hydration suppression, hydrogen absorption stabilization, and defect repair at the defect interface. This addresses the problem that existing low-impedance electrolytes rely solely on component blending and lack sufficient adaptive repair capabilities at the defect interface. Summary of the Invention

[0007] To address the aforementioned problems, this invention provides a branched organic ammonium salt electrolyte for low-impedance aluminum electrolytic capacitors, which effectively overcomes the shortcomings of existing technologies.

[0008] This invention is achieved through the following technical solution: a branched organic ammonium salt electrolyte for low-impedance aluminum electrolytic capacitors, comprising, by weight, the following components: 55-82 parts of a composite solvent, 2-8 parts of an ether-containing dicarboxylic acid, 4-14 parts of a branched long-chain dicarboxylic acid, 4-16 parts of a branched organic amine, 0.4-3.0 parts of a boron-containing polyhydroxy complexing component, 0.2-1.8 parts of a phosphorus-containing hydration-inhibiting component, 0.1-1.0 parts of a hydrogen absorption-stabilizing component, and 0.05-0.6 parts of a free radical inhibiting component; The ether-containing oxydicarboxylic acid, the branched long-chain dicarboxylic acid, and the branched organic amine form a branched organic ammonium salt conductive system. The branched organic ammonium salt conductive system simultaneously contains branched organic ammonium cations, ether-containing oxydicarboxylic acid groups, branched long-chain dicarboxylic acid groups, and unneutralized carboxyl groups. The degree of carboxyl neutralization of the branched organic ammonium salt conductive system is 52% to 78%. The branched organic ammonium cation has an ammonium nitrogen conductive end, a hydroxyl or ether oxygen association end, and a branched hydrocarbon shielding end. The ammonium nitrogen conductive end is used to form a dissociable ion pair with the ether-containing oxygen dicarboxylate ion and the branched long-chain dicarboxylate ion. The branched hydrocarbon shielding end is used to block the orderly crystallization of the ether-containing oxygen dicarboxylate ion and the branched long-chain dicarboxylate ion, so as to form a continuous ion conductive channel in the electrolytic liquid phase. The unneutralized carboxyl group and the boron-containing polyhydroxy complexing component together constitute defect interface complexing sites, which are used to form carboxylate-boron-oxygen complex structures with aluminum ions at the defects of the anodic oxide film of aluminum electrolytic capacitors. The branched organic ammonium cation can also form hydrogen bond association with the unneutralized carboxyl group in the defect interface complexation site through the hydroxyl or ether oxygen association end, and form dipole or hydrogen bond synergistic association with the boron-containing polyhydroxy complexation component in the defect interface complexation site, so that the branched organic ammonium cation forms an interface orientation layer at the anodic oxide film defect site with the ammonium nitrogen conductive end facing the anodic oxide film and the branched hydrocarbon shielding end facing away from the anodic oxide film; The interface orientation layer is used to retain local electrolyte at defects in the anodic oxide film and to inhibit the drying of electrolyte at the defects. The same branched organic ammonium salt conductive system is used to reduce impedance in the electrolyte liquid phase and to retain electrolyte and repair defects at the interface in the anodic oxide film.

[0009] As a preferred technical solution, the degree of carboxyl neutralization is formed by controlling the amount of carboxyl groups added by the branched organic amine relative to the total carboxyl groups of the ether-containing oxydicarboxylic acid and the branched long-chain dicarboxylic acid, so that unneutralized carboxyl groups are retained in the branched organic ammonium salt conductive system. The unneutralized carboxyl groups do not exist as free acidic additives, but are distributed in the ion-associated structure of the branched organic ammonium salt conductive system.

[0010] As a preferred technical solution, the branched organic amine is an organic amine containing at least one C3-C10 branched hydrocarbon group and at least one hydroxyalkyl or etheroxyalkyl group; the branched hydrocarbon group is used to reduce the crystallization tendency of the carboxylate conductive component, and the hydroxyalkyl or etheroxyalkyl group is used to form hydrogen bond association with the etheroxydicarboxylate group, the unneutralized carboxyl group or the boron-containing polyhydroxy complex component.

[0011] As a preferred technical solution, the branched organic amine is selected from one or more of diisopropylhydroxyethylamine, diisobutylhydroxyethylamine, isopropyl dihydroxyethylamine, branched alkylmorpholine, and branched alkylpiperidine.

[0012] As a preferred technical solution, the ether-containing oxygen dicarboxylic acid is a dicarboxylic acid containing 1 to 4 ether oxygen atoms in its molecular chain, and the branched long-chain dicarboxylic acid is a dicarboxylic acid with 8 to 18 carbon atoms and C1 to C8 branches at the α or β position; the molar ratio of the ether-containing oxygen dicarboxylic acid to the branched long-chain dicarboxylic acid is 1:0.6 to 3.5.

[0013] As a preferred technical solution, the composite solvent includes a first polar alcohol solvent, a second low-viscosity aprotic solvent, and a third high-boiling-point ether oxygen solvent; the first polar alcohol solvent is used to increase the ion dissociation degree of the branched organic ammonium salt conductive system, the second low-viscosity aprotic solvent is used to reduce the viscosity of the electrolyte, and the third high-boiling-point ether oxygen solvent is used to form an outer solvation structure with the hydroxyl or ether oxygen association end of the branched organic ammonium cation.

[0014] As a preferred technical solution, the first polar alcohol solvent includes one or more of ethylene glycol, diethylene glycol, propylene glycol, and glycerol; the second low-viscosity aprotic solvent includes one or more of γ-butyrolactone, N-methylpyrrolidone, dimethylformamide, and dimethylacetamide; and the third high-boiling-point ether oxygen solvent includes one or more of polyethylene glycol dimethyl ether, triethylene glycol monomethyl ether, and tetraethylene glycol dimethyl ether.

[0015] As a preferred technical solution, the boron-containing polyhydroxy complex component includes one or more of boron esterified polyol, boronized polyether polyol, and boric acid-polyhydroxycarboxylic acid complex; the boron-containing polyhydroxy complex component is used to improve the flashover voltage in the electrolytic liquid phase, and forms the carboxylate-boron-oxygen complex structure together with the unneutralized carboxyl groups at the defects of the anodic oxide film.

[0016] As a preferred technical solution, the phosphorus-containing hydration inhibiting component includes one or more of phosphate esters, phosphites, hydroxy phosphates, or ether oxyphosphates; the phosphorus-containing hydration inhibiting component is distributed in the outer solvation structure of the branched organic ammonium cation through hydrogen bonding or ion association, and can be enriched at the anodic oxide film defects according to the interfacial orientation of the branched organic ammonium cation, so as to inhibit the hydration reaction at the anodic oxide film defects.

[0017] As a preferred technical solution, the hydrogen absorption stabilizing component includes one or more of nitro aromatic compounds, quinoline compounds, anthraquinone compounds, or nitrogen-containing heterocyclic hydrogen absorption compounds; the hydrogen absorption stabilizing component and the phosphorus-containing hydration inhibiting component are distributed together in the interface orientation layer, so that the defects of the anodic oxide film simultaneously form a liquid retention, hydration inhibition, and hydrogen absorption stabilizing effect.

[0018] The beneficial effects of this invention are as follows: The low-impedance aluminum electrolytic capacitor electrolyte provided by this invention contains a branched organic ammonium salt electrolyte system formed by ether-oxydicarboxylic acid, branched long-chain dicarboxylic acid, and branched organic amines. This conductive system simultaneously contains branched organic ammonium cations, ether-oxydicarboxylic acid ions, branched long-chain dicarboxylic acid ions, and unneutralized carboxyl groups. The branched organic ammonium cations can form dissociable ion pairs with dicarboxylic acid ions in the electrolyte liquid phase. The ether-oxydicarboxylic acid ions are beneficial for improving ion dissociation and chain segment flexibility, while the branched long-chain dicarboxylic acid ions are beneficial for improving heat resistance stability. Furthermore, the branched hydrocarbon shielding ends of the branched organic ammonium cations can prevent the orderly crystallization and accumulation of dicarboxylic acid salts, thereby forming a more continuous and stable ion-conducting channel in the pores of the isolation paper and the electrolyte liquid phase, reducing the equivalent series resistance of the aluminum electrolytic capacitor.

[0019] This invention does not simply reduce impedance by increasing the content of conductive salts, but rather utilizes the ammonium-nitrogen conductive ends, hydroxyl or ether-oxygen association ends, and branched hydrocarbon shielding ends of branched organic ammonium cations to form a multifunctional linked structure. Under normal operating conditions, these branched organic ammonium cations primarily participate in bulk ion conduction and low-crystallinity stability. When localized temperature rises, acid value increases, or aluminum ion migration occur in the defect region of the anodic oxide film, they can form hydrogen bonds with unneutralized carboxyl groups at the defect interface complexation sites through the hydroxyl or ether-oxygen association ends, and form dipole or hydrogen bond synergistic associations with boron-containing polyhydroxy complex components, thereby forming oriented enrichment at the defect interface. Thus, the same branched organic ammonium salt conductive system can exert bulk impedance reduction and interface liquid retention and repair functions under different operating conditions, achieving a dual-state linkage between conductivity and defect interface stabilization functions.

[0020] This invention retains a certain proportion of unneutralized carboxyl groups in a branched organic ammonium salt conductive system, ensuring that these unneutralized carboxyl groups are not isolated as ordinary acidic additives but rather distributed within the ion-associated structure. When aluminum ions are generated at defects in the anodic oxide film, the unneutralized carboxyl groups can combine with boron-containing polyhydroxy complexing components to form defect interface complexation sites, further forming a carboxylate-boron-oxygen complex structure. This structure can form a local repair layer in the defect region, improving the interfacial stability at the oxide film defects and reducing the increase in leakage current and impedance rebound caused by the continuous expansion of defects.

[0021] The branched organic ammonium cations in this invention can form an interface orientation layer at the defect interface, with the ammonium nitrogen conductive ends facing the anodic oxide film and the branched hydrocarbon shielding ends facing away from the anodic oxide film. This interface orientation layer can, on the one hand, maintain the local electrolyte near the defect, reducing the risk of local drying caused by continuous heating in the defect area; on the other hand, it can form a certain interface barrier through the branched hydrocarbon shielding ends, slowing down the continuous accumulation of moisture, by-reactants, and gases at the defect, thereby improving the working stability of the capacitor under high-frequency ripple and high-temperature environments.

[0022] This invention utilizes the synergistic effect of a first polar alcohol solvent, a second low-viscosity aprotic solvent, and a third high-boiling-point ether-oxygen solvent in a composite solvent to achieve an electrolyte with both high ion dissociation, low system viscosity, and good high-temperature liquid retention. Specifically, the first polar alcohol solvent enhances the dissociation capability of the branched organic ammonium salt conductive system; the second low-viscosity aprotic solvent improves low-temperature impedance and reduces viscosity; and the third high-boiling-point ether-oxygen solvent forms an outer solvation structure with the hydroxyl or ether-oxygen association ends of the branched organic ammonium cations, enabling reversible switching between the bulk dispersed conductive state and the defect interface orientation enrichment state of the branched organic ammonium cations.

[0023] In this invention, the phosphorus-containing hydration-inhibiting component and the hydrogen-absorbing stabilizing component do not exist merely as independent additives, but are distributed within the outer solvation structure of the branched organic ammonium cations through hydrogen bonding or ion association. When the branched organic ammonium cations form an interfacial orientation layer at the defects in the anodic oxide film, the phosphorus-containing hydration-inhibiting component and the hydrogen-absorbing stabilizing component accumulate near the defect interface, respectively inhibiting the oxide film hydration reaction and inhibiting hydrogen accumulation. This allows the defect interface to simultaneously achieve a comprehensive effect of liquid retention, hydration inhibition, hydrogen absorption stabilization, and complexation repair.

[0024] Therefore, this invention can achieve a comprehensive improvement in low impedance, high liquid retention, low crystallization tendency, stable oxide film defect interface, and long lifespan at high temperatures without simply relying on increasing the conductive salt content. Compared with existing technologies where conductive salts, solvents, and additives function independently, the branched organic ammonium salt conductive system of this invention has a synergistic effect between bulk conductivity and defect interface repair, making it better suited for low impedance, high ripple, and long lifespan aluminum electrolytic capacitors. Attached Figure Description

[0025] To more clearly illustrate the technical solutions in the embodiments of the present invention or the prior art, the drawings used in the description of the embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.

[0026] Figure 1 This is a block diagram illustrating the composition and dual-state linkage of the branched organic ammonium salt electrolyte for the low-impedance aluminum electrolytic capacitor of the present invention. Figure 2 This is a three-terminal functional block diagram of the branched organic ammonium cation in this invention; Figure 3 This is a flowchart illustrating the formation of a continuous ion-conducting channel in the bulk phase in this invention. Figure 4 This is a flowchart of the defect interface liquid retention repair process in this invention; Figure 5 This is a block diagram illustrating the synergistic effect of key components in this invention; Figure 6 This is a block diagram illustrating the synergistic effect of the composite solvent in this invention. Detailed Implementation

[0027] All features disclosed in this specification, or all steps in all disclosed methods or processes, may be combined in any way, except for mutually exclusive features and / or steps.

[0028] Any feature disclosed in this specification (including any appended claims, abstract, and drawings) may be replaced by other equivalent or similar features for a similar purpose, unless specifically stated otherwise. That is, unless specifically stated otherwise, each feature is merely one example of a series of equivalent or similar features.

[0029] like Figures 1-6 As shown, this invention provides a branched organic ammonium salt electrolyte for low-impedance aluminum electrolytic capacitors. It can be used for impregnating the core of aluminum electrolytic capacitors and as the working medium for low-impedance, high-ripple, and long-life aluminum electrolytic capacitors. The electrolyte, by weight, includes a composite solvent, an ether-containing dicarboxylic acid, a branched long-chain dicarboxylic acid, a branched organic amine, a boron-containing polyhydroxy complexing component, a phosphorus-containing hydration-inhibiting component, a hydrogen-absorbing stabilizing component, and a free radical inhibiting component. The components do not simply function through mixing; rather, they form a branched organic ammonium salt conductive system in the electrolyte. This system creates continuous ionic conductive channels in the electrolyte liquid phase and forms an interface orientation layer at local defects in the anodic oxide film of the aluminum electrolytic capacitor. Thus, the same conductive system simultaneously provides phase resistance reduction, interface liquid retention, and defect repair.

[0030] In one embodiment, the electrolyte comprises, by weight, 55 to 82 parts of a composite solvent, 2 to 8 parts of an ether-containing dicarboxylic acid, 4 to 14 parts of a branched long-chain dicarboxylic acid, 4 to 16 parts of a branched organic amine, 0.4 to 3.0 parts of a boron-containing polyhydroxy complexing component, 0.2 to 1.8 parts of a phosphorus-containing hydration-inhibiting component, 0.1 to 1.0 parts of a hydrogen-absorbing stabilizing component, and 0.05 to 0.6 parts of a free radical inhibiting component. The composite solvent provides the basic dissolution medium and ion migration environment for the electrolyte. The ether-containing dicarboxylic acid and the branched long-chain dicarboxylic acid provide carboxyl group conductive sites and unneutralized carboxyl group complexing sites. The branched organic amine forms a branched organic ammonium salt conductive system with the dicarboxylic acid. The boron-containing polyhydroxy complexing component forms a defect interface complex structure in conjunction with the unneutralized carboxyl groups. The phosphorus-containing hydration-inhibiting component inhibits hydration side reactions in the anodic oxide film. The hydrogen-absorbing stabilizing component reduces the risk of hydrogen accumulation. The free radical inhibiting component inhibits thermal oxidation side reactions of the electrolyte under high temperature and high ripple conditions.

[0031] The ether-containing oxydicarboxylic acid, branched long-chain dicarboxylic acid, and branched organic amine form a branched organic ammonium salt conductive system in the electrolyte. This conductive system is not a completely neutralized system; rather, the degree of carboxyl neutralization is maintained between 52% and 78% by controlling the amount of branched organic amine relative to the total carboxyl groups. Through this degree of neutralization control, the electrolyte contains both branched organic ammonium cations, ether-containing oxydicarboxylic acid ions, and branched long-chain dicarboxylic acid ions that can participate in ion conduction, as well as a certain number of unneutralized carboxyl groups. These unneutralized carboxyl groups are not simply free acidic additives but are distributed within the ion-associative structure of the branched organic ammonium salt conductive system. Therefore, they do not significantly disrupt the stability of the electrolyte in the bulk phase but can provide local complexation sites when aluminum ions appear in defect regions of the anolyte film.

[0032] The branched organic ammonium cations are formed by the reaction of branched organic amines with ether-containing dicarboxylic acids and branched long-chain dicarboxylic acids. The branched organic ammonium cations possess ammonium-nitrogen conductive ends, hydroxyl or ether-oxygen association ends, and branched hydrocarbon shielding ends. The ammonium-nitrogen conductive ends can form dissociable ion pairs with ether-containing dicarboxylic acid ions and branched long-chain dicarboxylic acid ions, giving the electrolyte good ion conductivity in the bulk phase. The hydroxyl or ether-oxygen association ends can form hydrogen bonds or dipole associations with ether-containing dicarboxylic acid ions, unneutralized carboxyl groups, boron-containing polyhydroxy complex components, or ether-oxygen solvents in the complex solvent. Specifically, at defect interfaces, the hydroxyl or ether-oxygen association ends preferentially form hydrogen bonds with unneutralized carboxyl groups at the defect interface complexation sites and form synergistic associations with boron-containing polyhydroxy complex components, maintaining good solvation dispersion of the branched organic ammonium cations in the bulk phase and providing a basis for directional enrichment at defect interfaces. The branched hydrocarbon shielding end can block the regular arrangement between dicarboxylate salts, reduce the crystallization tendency of the conductive system containing branched organic ammonium salts, and avoid problems such as salting out, crystallization or interruption of conductive channels after the electrolyte is stored at low temperature or long-term high temperature.

[0033] The ether-oxygen-containing dicarboxylic acid can be selected from dicarboxylic acids containing one to four ether oxygen atoms in its molecular chain, such as diethylene glycol, triethylene glycol dicarboxylic acids, polyether dicarboxylic acids, or combinations thereof. The ether oxygen segment in the ether-oxygen-containing dicarboxylic acid can improve the solubility and chain flexibility of the carboxylate salt in the composite solvent, making it easier for the formed dicarboxylate group to form a dissociable ion pair with the branched organic ammonium cation. The branched long-chain dicarboxylic acid can be selected from dicarboxylic acids with eight to eighteen carbon atoms and one to eight carbon atom branches at the α- or β-position, such as branched azelaic acid, branched sebacic acid, branched dodecanoic acid, branched tetradecanoic acid, or combinations thereof. Branched long-chain dicarboxylic acids can improve the stability of the conductive salt system at high temperatures and further disrupt the ordered stacking of carboxylate salt crystals through their branched structure, thereby enhancing the low-impedance stability of the electrolyte. The molar ratio of ether-containing oxydicarboxylic acid to branched long-chain dicarboxylic acid can be controlled to be 1:0.6 to 1:3.5, so that the electrolyte can simultaneously take into account ion dissociation ability, heat resistance stability and low crystallization tendency.

[0034] The branched organic amine is an organic amine containing at least one branched hydrocarbon group with three to ten carbon atoms and at least one hydroxyalkyl or etheroxyalkyl group. The branched hydrocarbon group can be isopropyl, isobutyl, sec-butyl, tert-butyl, isopentyl, branched hexyl, or branched octyl; the hydroxyalkyl group can be hydroxyethyl, hydroxypropyl, or hydroxybutyl; and the etheroxyalkyl group can be methoxyethyl, ethoxyethyl, diethylene glycol, or triethylene glycol. Specifically, the branched organic amine can be selected from one or more of diisopropylhydroxyethylamine, diisobutylhydroxyethylamine, isopropyl dihydroxyethylamine, branched alkylmorpholine, and branched alkylpiperidine. The branched organic ammonium cations formed by this type of branched organic amine can exert electrical conductivity and decrystallization effects in the electrolytic liquid phase, and can also participate in interfacial orientation enrichment at anodic oxide film defects through hydroxyl or etheroxy association ends, thus forming a dual-state linkage effect that is different from ordinary straight-chain ammonium salts or simple quaternary ammonium salts.

[0035] The composite solvent comprises a first polar alcohol solvent, a second low-viscosity aprotic solvent, and a third high-boiling-point ether oxygen solvent. The first polar alcohol solvent is used to increase the ion dissociation degree of the branched organic ammonium salt conductive system, and may include one or more of ethylene glycol, diethylene glycol, propylene glycol, and glycerol. The second low-viscosity aprotic solvent is used to reduce the electrolyte viscosity and improve low-temperature impedance, and may include one or more of γ-butyrolactone, N-methylpyrrolidone, dimethylformamide, and dimethylacetamide. The third high-boiling-point ether oxygen solvent is used to form an outer solvation structure with the hydroxyl or ether oxygen association ends of the branched organic ammonium cations, and may include one or more of polyethylene glycol dimethyl ether, triethylene glycol monomethyl ether, and tetraethylene glycol dimethyl ether. Through the combination of these three types of solvents, the electrolyte can simultaneously possess high ion dissociation degree, low viscosity, and good high-temperature liquid retention capacity, and support the conversion between the branched organic ammonium cations in the bulk dispersion conductive state and the defect interface orientation state.

[0036] The boron-containing polyhydroxy complex component may include one or more of boron esterified polyols, boronized polyether polyols, and boric acid-polyhydroxycarboxylic acid complexes. In the electrolyte liquid phase, the boron-containing polyhydroxy complex component can improve the flash voltage and enhance the electrolyte's withstand voltage stability. At local defects in the anodic oxide film, due to potential localized temperature rises, acid value changes, and aluminum ion migration in the defect area, the boron-containing polyhydroxy complex component can form a complexation site at the defect interface with unneutralized carboxyl groups and form a carboxylate-boron oxide complex structure with aluminum ions. This structure can form a local interface repair layer in the defect area, reducing further expansion of the defect area and lowering the risk of increased leakage current and impedance rebound.

[0037] The phosphorus-containing hydration-inhibiting component may include one or more of phosphate esters, phosphites, hydroxyphosphates, or ether oxyphosphates. This component can be distributed within the solvated structure of the branched organic ammonium cations via hydrogen bonding or ionic association. When a localized temperature rise or increased hydration tendency occurs at the defects in the anodic oxide film, the branched organic ammonium cations are directionally enriched in the defect region. The phosphorus-containing hydration-inhibiting component can be carried into the vicinity of the defect interface during this directional enrichment process, thereby inhibiting the hydration reaction of the anodic oxide film at the defect site and reducing oxide film degradation.

[0038] The hydrogen-absorbing stabilizing component may include one or more of nitro aromatic compounds, quinoline compounds, anthraquinone compounds, or nitrogen-containing heterocyclic hydrogen-absorbing compounds. Specifically, it may be p-nitrobenzoic acid, nitrophenol, nitroanisole, octahydroxyquinoline, quinoline derivatives, anthraquinones, or nitrogen-containing heterocyclic hydrogen-absorbing stabilizers. The hydrogen-absorbing stabilizing component can inhibit the accumulation of hydrogen gas generated by the electrolyte under conditions of high temperature, leakage current, or electrochemical side reactions, and is distributed together with the phosphorus-containing hydration-inhibiting component in the interfacial orientation layer, thus simultaneously forming a liquid-retaining, hydration-inhibiting, and hydrogen-absorbing stabilizing effect at the defects in the anodic oxide film. The free radical inhibiting component may be a hindered phenolic antioxidant, benzotriazole compound, hydroquinone derivative, or phosphite antioxidant, which is used to inhibit the oxidative cracking of the electrolyte during long-term high-temperature operation, improving the thermal stability and lifetime stability of the electrolyte.

[0039] The electrolyte of this invention can be prepared as follows: First, a composite solvent is added to a reaction vessel and stirred and heated under nitrogen protection or other inert atmosphere to maintain the system temperature at 80 to 120 degrees Celsius. Then, ether-containing oxydicarboxylic acid and branched long-chain dicarboxylic acid are added, allowing them to fully dissolve or uniformly disperse in the composite solvent. After the dicarboxylic acid components are uniformly dispersed, a branched organic amine is slowly added for neutralization, and the total carboxyl group neutralization degree is maintained at 52% to 78% by controlling the amount of branched organic amine added. After neutralization, stirring and maintaining the temperature continue, allowing the branched organic ammonium cations, ether-containing oxydicarboxylic acid ions, branched long-chain dicarboxylic acid ions, and unneutralized carboxyl groups to form a stable ion-associative structure. Then, a boron-containing polyhydroxy complexing component, a phosphorus-containing hydration inhibitory component, a hydrogen absorption stabilizing component, and a free radical inhibitory component are added sequentially, and stirred uniformly at 80 to 110 degrees Celsius. Finally, the system is dehydrated, filtered, and cooled to obtain a branched organic ammonium salt electrolyte for low-impedance aluminum electrolytic capacitors.

[0040] In the electrolyte liquid phase, branched organic ammonium cations form dissociable ion pairs with ether-containing dicarboxylate ions and branched long-chain dicarboxylate ions. The composite solvent provides an outer solvation environment for these dissociable ion pairs, enabling the ions to migrate continuously within the pores of the separating paper and the electrolyte liquid phase. Because the branched organic ammonium cations have branched hydrocarbon shielding ends, dicarboxylate salts are less likely to form regular stacking or crystalline regions. Therefore, the electrolyte maintains good conductivity continuity under low temperature and long-term operating conditions. This effect differs from simply increasing the conductive salt content to reduce drag, and it reduces the viscosity increase, salting out, or high-temperature side reactions caused by excessive conductive salt.

[0041] When aluminum electrolytic capacitors operate under high-frequency ripple current, high temperature, or leakage current, localized temperature rises and acid value changes may occur in the defective areas of the anodic oxide film, accompanied by a small amount of aluminum ion migration. At this time, unneutralized carboxyl groups distributed in the branched organic ammonium salt conductive system can jointly capture aluminum ions with boron-containing polyhydroxy complexing components, forming a carboxylate-boron-oxygen complex structure. Simultaneously, branched organic ammonium cations form hydrogen bonds with unneutralized carboxyl groups at the defect interface complexation sites through their hydroxyl or ether oxygen association ends, and form dipole or hydrogen bond synergistic associations with the boron-containing polyhydroxy complexing components. This causes the branched organic ammonium cations to be directionally enriched at the defect interface, forming an interface orientation layer with the ammonium nitrogen conductive ends facing the anodic oxide film and the branched hydrocarbon shielding ends facing away from the anodic oxide film. This interface orientation layer can maintain local electrolyte at the defect site, inhibiting electrolyte drying due to continuous heating in the defect area, while simultaneously inhibiting hydration reactions and hydrogen accumulation in conjunction with phosphorus-containing hydration inhibitors and hydrogen-absorbing stabilizers.

[0042] Therefore, the branched organic ammonium salt conductive system in this invention exhibits a dual-state linkage effect. Under normal bulk conductive conditions, this system primarily forms continuous ion-conducting channels and reduces electrolyte impedance. Under anodic oxide film defect conditions, this system transforms into an interface liquid-retaining and defect-repairing system, simultaneously providing liquid retention, hydration suppression, hydrogen absorption stabilization, and complexation repair effects at the defect site. This dual-state linkage mechanism transforms the electrolyte from a simple performance additive combination of conductive salts, solvents, and additives into a system where the same branched organic ammonium salt conductive system generates different functions under different operating conditions, thereby improving the reliability of aluminum electrolytic capacitors under low impedance, high ripple, and high-temperature long-term operating conditions.

[0043] In one specific embodiment, the electrolyte comprises, by weight, 30 parts ethylene glycol, 20 parts γ-butyrolactone, 15 parts triethylene glycol monomethyl ether, 5 parts diethylene glycol, 9 parts branched sebacic acid, 10 parts diisopropylhydroxyethylamine, 1.2 parts borate esterified polyol, 0.8 parts ether-containing oxyphosphate, 0.3 parts nitro aromatic compound, and 0.1 parts hindered phenolic free radical inhibitor. The electrolyte is prepared by neutralization, complexation, stirring, dehydration, and filtration of the above components. The degree of carboxyl neutralization of the branched organic ammonium salt conductive system in this electrolyte is controlled at approximately 65%, which enables the formation of stable ion-conducting channels while maintaining low viscosity, and the formation of an interfacial orientation layer at defects in the anolyte film.

[0044] In another specific embodiment, the electrolyte comprises, by weight, 28 parts diethylene glycol, 18 parts N-methylpyrrolidone, 12 parts polyethylene glycol dimethyl ether, 6 parts ether-containing oxypolyether dicarboxylic acid, 10 parts branched dodecanoic acid, 12 parts isopropyl dihydroxyethylamine, 1.5 parts boric acid-polyhydroxycarboxylic acid complex, 1.0 parts phosphite, 0.4 parts quinoline-based hydrogen-absorbing stabilizer, and 0.15 parts hydroquinone derivative. In this embodiment, the branched organic ammonium cation exhibits strong hydroxyl association ability, which enhances its association stability with unneutralized carboxyl groups, boron-containing polyhydroxy complex components, and ether-oxygen solvents, making it suitable for high-temperature, long-life aluminum electrolytic capacitors.

[0045] In another specific embodiment, the electrolyte comprises, by weight, 25 parts propylene glycol, 22 parts γ-butyrolactone, 10 parts tetraethylene glycol dimethyl ether, 4 parts triethylene glycol dicarboxylic acid, 12 parts branched tetradecanoic acid, 13 parts branched alkyl morpholine, 2.0 parts borate-modified polyether polyol, 1.2 parts hydroxyphosphate, 0.5 parts anthraquinone hydrogen-absorbing stabilizer, and 0.2 parts benzotriazole free radical inhibitor. In this embodiment, the higher proportion of branched long-chain dicarboxylic acids is beneficial for improving the thermal stability of the electrolyte under high-temperature ripple conditions. Simultaneously, the ether-containing oxydicarboxylic acid and the composite solvent maintain ion dissociation capacity, preventing a significant increase in impedance due to the increase in long-chain components.

[0046] Further life tests were conducted, including 100 cycles of high and low temperature cycling from -40℃ to 105℃ and 2,000 hours of continuous power-on at 105℃. After the high and low temperature cycling, the equivalent series resistance change rates for Specific Examples 1, 2, 3, and the comparative example were 12.4%, 13.1%, 14.0%, and 31.8%, respectively. After 2,000 hours of continuous power-on at 105℃, the equivalent series resistance growth rates for Specific Examples 1, 2, 3, and the comparative example were 15.8%, 17.3%, 18.9%, and 42.6%, respectively; the leakage current growth rates were 9.6%, 10.8%, 12.1%, and 35.4%, respectively; and the capacity retention rates were 93.8%, 92.9%, 91.7%, and 84.2%, respectively. The above comparative results show that the defect interface complexation sites formed by the unneutralized carboxyl group and the boron-containing polyhydroxy complexing component can provide a stable carboxylate-boron-oxygen complex structure at the oxide film defect. The branched organic ammonium cations form an interface orientation layer through explicit hydrogen bonding association with the unneutralized carboxyl group and synergistic association with the boron-containing polyhydroxy complexing component, which enables the defect area to obtain liquid retention, hydration inhibition, hydrogen absorption stabilization and repair effects, thereby effectively reducing impedance rebound and leakage current growth.

[0047] Tests showed that at 25°C, the electrolyte conductivity of the electrolytes in Examples 1, 2, 3, and the comparative example was 8.6 mS / cm, 8.3 mS / cm, 8.1 mS / cm, and 6.7 mS / cm, respectively; at 20°C and 100 kHz, the equivalent series resistance of the corresponding capacitors was 18.6 mΩ, 19.4 mΩ, 20.1 mΩ, and 27.8 mΩ, respectively; and at -40°C and 100 kHz, the equivalent series resistance of the corresponding capacitors was 82.5 mΩ, 86.2 mΩ, 89.7 mΩ, and 138.4 mΩ, respectively. These results indicate that the branched hydrocarbon shielding end and the ether-oxygen association structure in the examples can reduce the ordered crystallization and low-temperature ion association of dicarboxylate, allowing the bulk continuous ion conductive channel to maintain good conductivity even at low temperatures.

[0048] To verify the aforementioned dual-state linkage effect of bulk conductivity and defect interface repair, the three specific embodiments were used to impregnate low-impedance aluminum electrolytic capacitor cores of the same specifications, and a comparative example was set up. The comparative example used a conventional low-impedance electrolyte formed from ethylene glycol, γ-butyrolactone, triethylene glycol monomethyl ether, ammonium sebacate, boric acid, ether-containing oxyphosphate, nitro aromatic compounds, and hindered phenolic free radical inhibitors. The comparative example did not use a branched organic ammonium salt conductive system formed from branched organic amines, ether-containing oxydicarboxylic acids, and branched long-chain dicarboxylic acids, nor did it control the degree of carboxyl neutralization to retain unneutralized carboxyl groups distributed in the ion-associated structure. All capacitors used the same anode foil, cathode foil, insulating paper, impregnation amount, sealing structure, and aging process to eliminate the influence of structural differences on the test results.

[0049] The above description is merely a specific embodiment of the present invention, but the scope of protection of the present invention is not limited thereto. Any changes or substitutions conceived without inventive effort should be included within the scope of protection of the present invention. Therefore, the scope of protection of the present invention should be determined by the scope defined in the claims.

Claims

1. A branched organic ammonium salt electrolyte for low-impedance aluminum electrolytic capacitors, characterized in that, By weight, it comprises the following components: 55-82 parts of complex solvent, 2-8 parts of ether-containing dicarboxylic acid, 4-14 parts of branched long-chain dicarboxylic acid, 4-16 parts of branched organic amine, 0.4-3.0 parts of boron-containing polyhydroxy complexing component, 0.2-1.8 parts of phosphorus-containing hydration inhibitory component, 0.1-1.0 parts of hydrogen absorption stabilizing component, and 0.05-0.6 parts of free radical inhibitory component; The ether-containing oxydicarboxylic acid, the branched long-chain dicarboxylic acid, and the branched organic amine form a branched organic ammonium salt conductive system. The branched organic ammonium salt conductive system simultaneously contains branched organic ammonium cations, ether-containing oxydicarboxylic acid groups, branched long-chain dicarboxylic acid groups, and unneutralized carboxyl groups. The degree of carboxyl neutralization of the branched organic ammonium salt conductive system is 52% to 78%. The branched organic ammonium cation has an ammonium nitrogen conductive end, a hydroxyl or ether oxygen association end, and a branched hydrocarbon shielding end. The ammonium nitrogen conductive end is used to form a dissociable ion pair with the ether-containing oxygen dicarboxylate ion and the branched long-chain dicarboxylate ion. The branched hydrocarbon shielding end is used to block the orderly crystallization of the ether-containing oxygen dicarboxylate ion and the branched long-chain dicarboxylate ion, so as to form a continuous ion conductive channel in the electrolytic liquid phase. The unneutralized carboxyl group and the boron-containing polyhydroxy complexing component together constitute defect interface complexing sites, which are used to form carboxylate-boron-oxygen complex structures with aluminum ions at the defects of the anodic oxide film of aluminum electrolytic capacitors. The branched organic ammonium cation can also form hydrogen bond association with the unneutralized carboxyl group in the defect interface complexation site through the hydroxyl or ether oxygen association end, and form dipole or hydrogen bond synergistic association with the boron-containing polyhydroxy complexation component in the defect interface complexation site, so that the branched organic ammonium cation forms an interface orientation layer at the anodic oxide film defect site with the ammonium nitrogen conductive end facing the anodic oxide film and the branched hydrocarbon shielding end facing away from the anodic oxide film; The interface orientation layer is used to retain local electrolyte at defects in the anodic oxide film and to inhibit the drying of electrolyte at the defects. The same branched organic ammonium salt conductive system is used to reduce impedance in the electrolyte liquid phase and to retain electrolyte and repair defects at the interface in the anodic oxide film.

2. The branched organic ammonium salt electrolyte for low-impedance aluminum electrolytic capacitors according to claim 1, characterized in that, The degree of carboxyl neutralization is formed by controlling the amount of carboxyl groups added by the branched organic amine relative to the total carboxyl groups of the ether-containing oxydicarboxylic acid and the branched long-chain dicarboxylic acid, so that unneutralized carboxyl groups are retained in the branched organic ammonium salt conductive system. The unneutralized carboxyl groups do not exist as free acidic additives, but are distributed in the ion-associated structure of the branched organic ammonium salt conductive system.

3. The branched organic ammonium salt electrolyte for low-impedance aluminum electrolytic capacitors according to claim 1, characterized in that, The branched organic amine is an organic amine containing at least one C3-C10 branched hydrocarbon group and at least one hydroxyalkyl or etheroxyalkyl group; the branched hydrocarbon group is used to reduce the crystallization tendency of the carboxylate conductive component, and the hydroxyalkyl or etheroxyalkyl group is used to form hydrogen bond association with the etheroxydicarboxylate group, the unneutralized carboxyl group, or the boron-containing polyhydroxy complex component.

4. The branched organic ammonium salt electrolyte for low-impedance aluminum electrolytic capacitors according to claim 3, characterized in that, The branched organic amine is selected from one or more of diisopropylhydroxyethylamine, diisobutylhydroxyethylamine, isopropyl dihydroxyethylamine, branched alkylmorpholine, and branched alkylpiperidine.

5. The branched organic ammonium salt electrolyte for low-impedance aluminum electrolytic capacitors according to claim 1, characterized in that, The ether-containing dicarboxylic acid is a dicarboxylic acid containing 1 to 4 ether oxygen atoms in its molecular chain, and the branched long-chain dicarboxylic acid is a dicarboxylic acid with 8 to 18 carbon atoms and C1 to C8 branches at the α or β position; the molar ratio of the ether-containing dicarboxylic acid to the branched long-chain dicarboxylic acid is 1:0.6 to 3.

5.

6. The branched organic ammonium salt electrolyte for low-impedance aluminum electrolytic capacitors according to claim 1, characterized in that, The composite solvent comprises a first polar alcohol solvent, a second low-viscosity aprotic solvent, and a third high-boiling-point ether oxygen solvent; the first polar alcohol solvent is used to increase the ion dissociation degree of the branched organic ammonium salt conductive system, the second low-viscosity aprotic solvent is used to reduce the viscosity of the electrolyte, and the third high-boiling-point ether oxygen solvent is used to form an outer solvation structure with the hydroxyl or ether oxygen association end of the branched organic ammonium cation.

7. The branched organic ammonium salt electrolyte for low-impedance aluminum electrolytic capacitors according to claim 6, characterized in that, The first polar alcohol solvent includes one or more of ethylene glycol, diethylene glycol, propylene glycol, and glycerol; the second low-viscosity aprotic solvent includes one or more of γ-butyrolactone, N-methylpyrrolidone, dimethylformamide, and dimethylacetamide; and the third high-boiling-point ether solvent includes one or more of polyethylene glycol dimethyl ether, triethylene glycol monomethyl ether, and tetraethylene glycol dimethyl ether.

8. The branched organic ammonium salt electrolyte for low-impedance aluminum electrolytic capacitors according to claim 1, characterized in that, The boron-containing polyhydroxy complex component includes one or more of borate esterified polyols, borate esterified polyether polyols, and boric acid-polyhydroxy carboxylic acid complexes; the boron-containing polyhydroxy complex component is used to improve the flashover voltage in the electrolytic liquid phase, and forms the carboxylate-boron oxide complex structure together with the unneutralized carboxyl groups at the defects of the anodic oxide film.

9. The branched organic ammonium salt electrolyte for low-impedance aluminum electrolytic capacitors according to claim 1, characterized in that, The phosphorus-containing hydration inhibitory component includes one or more of phosphate esters, phosphites, hydroxy phosphates, or ether oxyphosphates; the phosphorus-containing hydration inhibitory component is distributed in the outer solvation structure of the branched organic ammonium cation through hydrogen bonding or ion association, and can be enriched at the anodic oxide film defects according to the interfacial orientation of the branched organic ammonium cation, so as to inhibit the hydration reaction at the anodic oxide film defects.

10. The branched organic ammonium salt electrolyte for low-impedance aluminum electrolytic capacitors according to claim 1, characterized in that, The hydrogen-absorbing stabilizing component includes one or more of nitro aromatic compounds, quinoline compounds, anthraquinone compounds, or nitrogen-containing heterocyclic hydrogen-absorbing compounds; the hydrogen-absorbing stabilizing component and the phosphorus-containing hydration-inhibiting component are distributed together in the interface orientation layer, so that the defects of the anodic oxide film simultaneously form a liquid-retaining, hydration-inhibiting, and hydrogen-absorbing stabilizing effect.